AUTOPSY STUDY ON INCIDENCE OF METOPIC SUTURE IN BHAVNAGAR REGION OF GUJARAT - Bhabhor, Ritesh R; Parmar, Amit P (Journal of Forensic Medicine and Toxicology, 2019)
Introduction: Metopic suture which is placed between frontal bone and usually disappear during infancy and childhood, may persist from nasion to anterior angle of bregma, this is called metopism. Objective: To find the incidence of metopism in Bhavnagar region and to compare it with other study in other parts of India. Methodology: This study was carried out on 500 cases brought to mortuary complex of Sir T. General Hospital, Bhavnagar for post-mortem examination. Results: Two skulls (0.4%) had found metopic suture in the form of one complete metopic suture and another incomplete metopic suture. Thus metopism was observed in 0.4% cases. Conclusion: The presence of metopic suture simulates the fracture of frontal bone, therefore it should be properly ruled out in X-rays by radiologists and neurosurgeons.
Keywords: Metopic suture; Metopism; Frontal bone; Skull